Entrepreneurship : GEMMS / Armyza Shahrina Zainuddin ... [et al.] - Zainuddin, Armyza Shahrina; Mohamed, Fauziah; Ibrahim, Erda Irdiani; Hassan, Norhamimi Fauzana; Daud, Siti Suhaiza
GEMMS Sdn Bhd operates pest control services our company is private limited company. Our main objective is to satisfied customers’ needs and wants. Besides that, We want to protect our properties from destroying by these harmful insects.